Participatory museum strategies: reflecting and acting in Sociomuseology (Cadernos de Sociomuseologia, 2014)
This paper is based on my Master Dissertation, which is focused on a fieldwork carried out in a parish of Peniche, Portugal, based on a project designated 'Participatory Inventory of Cultural Heritage of Atouguia da Baleia’, associated with the implementation of a museum. It has as objective the inventory of cultural heritage in the different localities of this region, the strengthening of the relation museum-population and the recognition by the community of their assets, concerning the relationship between heritage and development. Developed as an action research project, this study was drawn with the knowledge of several scientific disciplines that contributed, with their theoretical framework and methodologies of action, for the selection of strategies and direction of the work developed in the field. Participation is central in the project. In this paper, we reflect about several issues, such as the centrality of community participation; the participatory inventory and the necessary recognition and appropriation of cultural heritage; the urgency of a dialogical thinking, where theory and practice are interlinked; the importance of interdisciplinarity in Sociomuseology; the succession of participative methods, which contributes to a better knowledge of the fieldwork and to the relation museum-community-territory; and the heritage education as a foundation to citizenship, development and cultural legacy valorisation.Keywords: Participatory inventory, Sociomuseology, Cultural heritage, Collective memory, Community development and participation